Productivity and rooting of olive mini-cuttings grown in a clonal mini-garden according to season - Casarin, Josiane Vergara; Moreira, Roseane Maidana; Raasch, Carlos Gustavo; Timm, Cari Rejane Fiss; Schuch, Márcia Wulff (Comunicata Scientiae, 2018)
The mini-cuttings productivity in clonal mini-garden using the semi-hydroponic system is a promising technique for the olive propagation, to obtaining a satisfactory amount of cuttings and with good quality. The objective was to evaluate the mini-stumps productivity and rooting of olive mini-cuttings in successive collections at different times of year in a clonal mini-garden in a semi-hydroponic system. In each collection the productivity of the clonal mini-garden was evaluated counting the collected cuttings. The mini-cuttings were prepared with 3-5 cm long with leaf area reduced by 50% and placed in plastic boxes with vermiculite for a period of 80 days. The evaluated variables were: mini-stumps productivity, mini-stumps and mini-cuttings percentage of survival, rooting percentage and number and length of mini-cuttings root. The olive mini-cuttings presented higher productivity during the spring of 2014. The mini-cuttings rooting percentage collected during the evaluated periods demonstrated that mini-cutting is a viable technique for olive propagation when grown in clonal mini-garden using a semi-hydroponic system.